Experiences of belonging: A comparative case study between China-domiciled and UK-domiciled students - Smith, Susan; Watson, Sarah (Journal of University Teaching and Learning Practice, 2022)
Different domiciled groups experience belonging differently within university contexts, with China-domiciled students studying in UK Business Schools often finding it more difficult to integrate into university culture than their European counterparts, partially contributing to the sector awarding gap between these groups studying Business and Management subjects. With recognition that the pandemic induced move to teaching online exacerbated challenges to belonging for all students, 17 Chinese and 16 UK finalist undergraduates were interviewed about their experiences of belonging before the pandemic, during the pandemic, and once face-to-face teaching had resumed. The research contributes to an increasingly nuanced understanding of the university habitus and its relationship to belonging as both contextual and temporal, revealing commonalities and differences in establishing a sense of belonging in heterogeneous student cohorts. The research extends the four domains of belonging; academic, social, surroundings and personal space to include the digital space, a previously unexplored dimension of student belonging that gained greater prevalence with the move to teaching online. The research uncovers the exclusionary effects of social media platform adoption and contextualises this inequality through ideas of digital habitus. Findings highlight the importance of the transition to Higher Education and the ongoing work required to foster a secure sense of belonging for all students, but particularly those who enter into university with a cultural background that is very different to the culture of the university.